Carbon-ion Radiotherapy for Isolated Lymph Node Metastasis After Surgery or Radiotherapy for Lung Cancer - Shirai, Katsuyuki; Kubota, Yoshiki; Ohno, Tatsuya; Saitoh, Jun-ichi; Abe, Takanori; Mizukami, Tatsuji; Mori, Yasumasa; Kawamura, Hidemasa; Akahane, Keiko; Nakano, Takashi (Frontiers in Oncology, 2019)
Purpose: Mediastinal and hilar lymph node metastasis is one of the recurrence patterns after definitive treatment of lung cancer. Salvage radiotherapy (RT) can be a treatment option for lymph node metastasis. However, the usefulness of additional RT remains unclear after surgery or RT for the primary lung tumor. We retrospectively evaluated the efficacy and safety of hypofractionated carbon-ion RT for isolated lymph node metastasis. Methods and Materials: Between April 2013 and August 2016, 15 consecutive patients with isolated lymph node metastasis underwent carbon-ion RT. The pretreatment evaluations confirmed the isolated lymph node metastasis and the absence of local recurrence or distant metastasis, which was oligometastatic disease. The median age was 72 (range, 51−83) years, with 11 male patients. The first treatments for primary lung tumors were carbon-ion RT for 8 patients and surgery for 7 patients. There were 9 adenocarcinomas, 4 squamous cell carcinomas, 1 adenosquamous cell carcinoma, and 1 mucoepidermoid carcinoma. Most patients (93%) were irradiated with 52.8 Gy relative biological effectiveness in 12 fractions for 3 weeks. There were no patients treated with concurrent or adjuvant therapy such as chemotherapy, molecular-targeted therapy, or immunotherapy. Adverse events were evaluated according to the Common Terminology Criteria for Adverse Events (version 4.0). Results: The median follow-up for surviving patients was 28 months. One patient experienced local lymph node recurrence, and the 2-year local control rate was 92% for all patients. Distant metastasis was observed in 7 patients, and 2-year progression-free survival rate was 47%. During follow-up, there were 4 deaths from lung cancer, and the 2-year overall survival rate was 75%. There were 2 patients with acute grade 2 esophagitis and 2 with late grade 2 cough, which were improved by conservative therapy. There were no other grade 2 or higher adverse events. Conclusions: Hypofractionated carbon-ion RT showed excellent local control and overall survival without severe toxicities in lung cancer patients with isolated lymph node metastasis after surgery or carbon-ion RT for primary lung tumors. A multi-institutional prospective study is required to establish the efficacy and safety of carbon-ion RT.